Phenotypic and Genotypic Characterization of ESBL Producing E. coli Isolates from the Ruminant Species of Namakkal Region, India - Javagar, Mouri; Ramya, K; Karthiga, D; Madhumitha, B; Thangavelu, A; Sukumar, K; Selvaraju, M (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Antibiotic resistance in animals is a significant and highly challenging threat among animals. Extended spectrum β-lactamase (ESBL)  producing E. coli amongst all bacteria have been categorized by the WHO as the most critical AMR pathogen to human health and a  major public health concern. In an effort to study the prevalence of ESBL producing coliforms among the ruminant species, phenotypic  screening and confirmation by Kirby Bauer diffusion method followed by genotypic characterization of the isolates were carried out  to ascertain the type of β-lactamase involved in conferring resistance. A total of 50 fecal swabs were collected from the cattle (n=26),  buffalo (n=11), goat (n=10) and sheep (n=3) species. A total of 72 (26/50) % and 68 (34/50) % of the coliform isolates from the ruminant  species were found to be phenotypically resistant to most of the β-lactam group of antibiotics and third generation cephalosporins,  respectively. The isolates showing phenotypic resistance to third generation cephalosporins were genotypically confirmed by multiplex  PCR to determine the types of β-lactamase coding for the resistance. The multiplex PCR for TEM, SHV and OXA type ESBLs revealed the  presence of 713 and 564 bp amplicon indicating the predominance of serine β-lactamases, viz., SHV (Class A) and OXA (Class D) type  ESBL in 85.7 % and 7.0 % of the coliform isolates of ruminants. This study confirms and emphasizes the prevalence of ESBL producing  coliforms and the hidden threat underlying in healthy ruminant species.
Keywords: Antimicrobial resistance; E. coli. Extended spectrum β-lactamase (ESBL); Genotypic; Multiplex PCR; Phenotypic